Effect of foliar treatment with salicylic acid and silicon on the resistance of eggplant to drought in sandy soil (Journal of Hama University, 2024)
The study was conducted at the Agricultural Scientific Research Center in the Sanobar Jableh region, in sandy soil, using eggplant plants (the Noria class), in order to study the effect of foliar spraying with salicylic acid (50-100-150 ppm) and silicon (100-150-200 ppm). In some indicators of vegetative and fruiting growth of eggplant plant and in water use efficiency.Spraying the plants with silicon and salicylic acid resulted in a significant increase in the number of leaves and the leaf surface area, as well as the dry weight of each of the branches and roots, as well as the number of flowers and fruit set and the percentage of set and production, compared with the control, and the most superior treatments were those in which the highest concentration of silicon and salicylic acid was used. .The water use efficiency (the amount of water required to produce 1 kg of fruits) increased as a result of the treatment with silicon and salicylic acid. The most superior treatment was Si3 (200 ppm), followed by Si2 and SA3 (150ppm).Also, the productivity of eggplant plant increased significantly by increasing the concentration of the spray solution in all treatments of spraying with silicone and salicylic acid over the control treatment, and the most superior treatment was Si3 followed by SA3 treatment.